Carry on thinking: Nurse education in the Corporate University - Rolfe, Gary (Nursing philosophy, 2019)
It is widely acknowledged that the modern university can be traced back to the inauguration of the University of Berlin in 1810. In the subsequent two centuries, the idea of the university has taken on many forms, largely driven by the political concerns of the day and often in response to demands from the electorate for greater state regulation and accountability for public spending. Until recently, the responsibility for academic and social legitimation had shifted between the church, the state and the university itself. However, in opening up the higher education sector to the influence of the market economy, the state has surrendered much of its political influence over the academic governance of the university to the power of the consumer, which is to say, to students. In this essay, I trace the history of the modern university and examine the significance and implications for nurse education of the turn towards the market. Drawing on the work of Derrida, Lyotard and Readings, I suggest that the return to liberal education is no longer possible, and argue instead for a philosophical strategy of subversion.